Investigation of Short-term Scenarios of Infectious and Medical Waste Management (Case Study: Kerman, Iran) - Abbas Ghavam; Hossein Vahidi (Environmental Energy and Economic Research)
Infectious and Medical Waste (IMW) management is one of the challenges of urban management in coronavirus pandemics. Many cities in Iran do not have the necessary infrastructure for rapid and emergency management of IMW in this time frame. Other challenges, such as increasing the generation rate of IMW and further contamination of this waste, increase the need for rapid and principled action. The IMW’s sources were divided into concentration and production volume: large and concentrated sources include hospitals, and small scattered sources include clinics and laboratories. To evaluate and choose the most proper short-time solution, after wide-field visits, different waste management scenarios were predicted. The final was selected by examining different indicators by the Analytical Hierarchy Process model. The main problem of IMW management in Kerman city is collecting and disposing of IMW in small and scattered centers supervised by the Medical Council of the Islamic Republic of Iran. According to the obtained results, the private contractor company collects hazardous waste from the clinics and laboratories and sends them to the hospitals' decontamination units. Then, Kerman Municipality receives the decontaminated waste from hospitals and transfers it to the particular burial landfill. The proposed scenario can certainly lead to a short-term problem of improving Kerman's IMWM, especially in the coronavirus pandemic, relying on the available facilities. Moreover, based on the sensitivity analysis, social indicators have the highest level, and financial indicators have the lowest sensitivity for the proposed solution.